A LOOK AT NATIONAL EDUCATION IN THE WORKS OF THE STORYTELLER TURMAGAMBET IZTILEUOV - Chengel, H.K.; Zhanbershieva, U.N.; Kudaibergenova, Kunimzhan (Pedagogy and Psychology, 2023)
In literary studies, we see that research on the works of Syr region storytellers has led to the joint writing of various new directions. The article reveals the scenes of national education and cognitive foundation in the works of Syr region storyteller T. Iztleuov. In other words, the influence of national education on the psyche of the nation, its mental attitudes, and imagery in a broad concept is taken entirely and interpreted as a pledge of education. It provides for the formation of the worldview of the younger generation, and the education of patriotism. It follows from this that the examples and aitys, the poems of T. Iztleuov are a poetic expression of the spirit of the nation. The culture, history, and education of the nation as a whole are preserved in the works of Syr region storytellers. It is also established that one of the main functions of education is morality. Therefore, taking the education of a person as an object, considering him in a scientific system, and taking into account the need to study his cognition and thinking depending on psychological units and didactic concepts, in our article we set a goal to analyze their paradigms.